2017
DOI: 10.1161/jaha.116.004880
|View full text |Cite
|
Sign up to set email alerts
|

Normalization of Testosterone Levels After Testosterone Replacement Therapy Is Associated With Decreased Incidence of Atrial Fibrillation

Abstract: BackgroundAtrial fibrillation (AF) is the most common cardiac dysrhythmia associated with significant morbidity and mortality. Several small studies have reported that low serum total testosterone (TT) levels were associated with a higher incidence of AF. In contrast, it is also reported that anabolic steroid use is associated with an increase in the risk of AF. To date, no study has explored the effect of testosterone normalization on new incidence of AF after testosterone replacement therapy (TRT) in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 48 publications
2
31
0
3
Order By: Relevance
“…Risks of adverse CV events were similar for untreated men and treated men without T normalization. This same group found that normalization of testosterone levels is associated with a decreased incidence of atrial fibrillation, a condition often associated with increased risk of stroke …”
Section: Review Of New CV Studiesmentioning
confidence: 95%
See 2 more Smart Citations
“…Risks of adverse CV events were similar for untreated men and treated men without T normalization. This same group found that normalization of testosterone levels is associated with a decreased incidence of atrial fibrillation, a condition often associated with increased risk of stroke …”
Section: Review Of New CV Studiesmentioning
confidence: 95%
“…Since the FDA advisory committee meeting in September 2014, 23 new studies published addressing CV risks of TTh. This includes 12 clinical trials and 11 observational data analyses . Five of these studies comprise the T Trials .…”
Section: Review Of New CV Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are few studies that have investigated the effect of TTh on arrhythmias. Sharma et al [ 45 ] studied whether normalization of serum T levels after TTh has an impact on the incidence of atrial fibrillation (Afib). They retrospectively compared patients at the US VA who received TTh and resulted in normalization of serum T (n=40,856), patients who received TTh without normalization of serum T (n=23,930), and those who did not receive TTh and continued to have low serum T (n=11,853).…”
Section: Emerging Evidencementioning
confidence: 99%
“…Sharma et al [ 45 ] highlighted that normalization of T levels is associated with a lower incidence of Afib in men with LOH. Although the mechanism by which normal T levels reduce the risk of Afib is still unclear, their study suggested that TTh may have antiarrhythmogenic properties.…”
Section: Emerging Evidencementioning
confidence: 99%